Analysis of microstructural effects on mechanical properties of copper alloys - Okayasua, Mitsuhiro (H. : ĐHQGHN, 2017)
With the aim of obtaining copper alloys with favorable mechanical properties (high strength and high ductility) for various engineering applications, the microstructural characteristics of two conventional copper alloysdan aluminum bronze (AlBC; CueAl9.3eFe3.8eNi2eMn0.8) and a brass (HB: CueAl4eZn25 eFe3eMn3.8)dand a recently developed aluminum bronze (CADZ: CueAl10.5eFe3.1eNi3.5eMn1.1eSn3.7), were controlled by subjecting the alloys to two different processes (rolling and casting) under various conditions. For the rolling process, the rolling rate and temperature were varied, whereas for the casting process, the solidification rate was varied. Microstructural characteristics, as examined by electron backscatter diffraction analysis, were found to differ among the alloys. Complicated microstructures formed in CADZ led to high hardness and high tensile strength (sUTS), but low ductility (εf). For CADZ, casting at a high solidification rate allowed an increase in ductility to be obtained as a result offine-grained structure and low internal stress. In contrast, high ductility (with a fracture strain of more than 30%) was found for both cast AlBC and cast HB; moreover, both of these alloys possessed high tensile strength when produced by warm rolling at 473 K. For CADZ, on the other hand, no clear effect of rolling on tensile strength could be found, owing to the many microcracks caused by its brittleness. The results of this study indicate that copper alloys with excellent mechanical properties can be produced. This is especially the case for the conventional alloys, with a high tensile strengthsUTS¼900 MPa and a high fracture strainεf ¼10% being obtained for warm-rolled brass.